Implementasi Program UN Women Women’s Empowerment Principles Melalui PT Amartha Mikro Fintek dalam Meningkatkan Kesetaraan Gender dan Pemberdayaan Perempuan di Indonesia Tahun 2020-2023 - Safila; Sintia Catur Sutantri; Risalatu Mirajiah; Widiandaru Wiryawan (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Indonesia is a country with a relatively high level of gender inequality. This condition is driven by persistent discrimination against women within the country. The United Nations, through its gender entity UN Women, plays an important role in addressing this issue. This study examines the problem of gender inequality in Indonesia and analyzes how an international organization positions itself as an actor in international relations to address the issue. The purpose of this study is to identify the role of UN Women as an international organization in promoting gender equality in Indonesia through one of its programs, the Women’s Empowerment Principles (WEPs), which have been implemented by PT Amartha Mikro Fintek as one of the companies in Indonesia. Using a qualitative research approach, this study analyzes the issue by applying Clive Archer’s theory of international organizations, as well as the concepts of gender equality and women’s empowerment. The data used in this study are secondary data obtained from books, academic journals, articles, documents, news magazines, newspapers, and data available on websites or the internet. The findings indicate that women’s empowerment in Indonesia continued to increase during the period 2020–2023. This progress cannot be separated from the role of UN Women in carrying out its functions as an international organization—both as an instrument, an arena, and an independent actor—through the WEPs program implemented by PT Amartha Mikro Fintek. Indonesia merupakan negara dengan tingkat ketidaksetaraan gender yang cukup tinggi. Hal ini disebabkan oleh adanya diskriminasi terhadap perempuan yang terjadi di negara tersebut. PBB melalui entitas gender UN Women turut memiliki andil dalam mengatasi masalah ini. Penelitian ini mengangkat masalah ketimpangan gender yang terjadi di Indonesia, serta bagaimana organisasi internasional memposisikan dirinya sebagai salah satu aktor hubungan internasional dalam mengatasi permasalahan tersebut. Penelitian ini bertujuan untuk mengetahui peran UN Women selaku organisasi internasional dalam mengatasi masalah kesetaraan gender di Indonesia melalui salah satu programnya WEPs yang diimplementasikan oleh PT Amartha Mikro Fintek sebagai salah satu perusahaan di Indonesia. Dalam penelitian kualitatif ini, penulis menganalisis masalah dengan menggunakan teori organisasi internasional dari Clive Archer, konsep kesetaraan gender dan pemberdayaan perempuan. Sumber data yang dipakai merupakan data sekunder yang diperoleh melalui buku, jurnal ilmiah, artikel, dokumen, majalah berita, surat kabar, maupun data-data yang terdapat di website atau internet. Hasil dari penelitian melihat pemberdayaan perempuan di Indonesia terus meningkat selama tahun 2020-2023, hal ini tidak terlepas UN Women dalam menjalankan perannya sebagai organisasi internasional, baik peran sebagai instrumen, arena, maupun aktor independen dengan program WEPs yang turut diimplementasikan oleh PT Amartha Mikro Fintek.